1995
DOI: 10.1210/en.136.5.1877
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of the modulation by glucose of hepatic gluconeogenesis in the genetically obese (fa/fa) Zucker rat

Abstract: Genetically obese (fa/fa) Zucker rats show oral glucose intolerance, an alteration that has been attributed at least in part to an impaired suppression of hepatic glucose output after the ingestion of glucose. In this work, we studied the influence of different concentrations of glucose (2.5-30 mM) on gluconeogenesis from a mixture of [14C]lactate-pyruvate as well as on fructose 2,6-bisphosphate levels, pyruvate kinase activity, and flux through the reaction catalyzed by 6-phosphofructo-1-kinase, in hepatocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1998
1998
2002
2002

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Gluconeogenesis has been reported to be lower in hepatocytes from obese Zucker rats, 13,14,30,31 in spite of the fact that phosphoenolpyruvate carboxykinase mRNA increases at similar levels than in lean animals. These results agree with the transcriptional activation of this gene reported previously.…”
Section: Discussionmentioning
confidence: 99%
“…Gluconeogenesis has been reported to be lower in hepatocytes from obese Zucker rats, 13,14,30,31 in spite of the fact that phosphoenolpyruvate carboxykinase mRNA increases at similar levels than in lean animals. These results agree with the transcriptional activation of this gene reported previously.…”
Section: Discussionmentioning
confidence: 99%
“…Exton & Park (2) used a saturating amount of lactate (30 mmol/l), which would have made it dif®cult to detect a small inhibition of gluconeogenesis. Conversely, it is possible that gluconeogenic substrates were limiting in the studies of Sa Ânchez-Gutie Ârrez et al (25) and Ruderman & Herrera (5). In the ®rst instance, the incubation medium provided 2 mmol/l lactate and 0.2 mmol/l pyruvate (25), while in the second, the perfusate supplied 1 mmol/l alanine (5).…”
Section: Journal Of Endocrinology (1998) 138mentioning
confidence: 99%
“…Conversely, it is possible that gluconeogenic substrates were limiting in the studies of Sa Ânchez-Gutie Ârrez et al (25) and Ruderman & Herrera (5). In the ®rst instance, the incubation medium provided 2 mmol/l lactate and 0.2 mmol/l pyruvate (25), while in the second, the perfusate supplied 1 mmol/l alanine (5). The duration of fasting (and thus the mass of glycogen available) may also determine whether suppression of gluconeogenesis occurs during hyperglycemia, or whether suppression of glycogenolysis is the primary response.…”
Section: Journal Of Endocrinology (1998) 138mentioning
confidence: 99%
See 1 more Smart Citation
“…Data from in vitro studies are similarly conflicting. A study in isolated rat hepatocytes by Sanchez-Gutierrez et al (31) indicated that hyperglycemia significantly inhibited gluconeogenesis. A study by Davidson (12), on the other hand, suggested that hyperglycemia did not do so.…”
mentioning
confidence: 99%